Control of the Balance between Vapor and Heat Transfer for the Reduction of Oxygen Transport Resistance in High Current Density PEFC Operation. (3rd July 2019) - Kitami, Yuki; Tabe, Yutaka; Chikahisa, Takemi
Abstract : This study confirmed the unusual increase in oxygen transport resistance at higher current densities during high temperature operation: the increase becomes more pronounced with the lower relative humidity of the supplied gas. To investigate the causes, we estimated the relative humidity in the catalyst layer (CL) using a vapor diffusion and heat conduction model, which shows drier state in the CL with higher current densities under the high temperature conditions. Water distribution in the cell after the unusual increase was also observed using freezing method, and it was confirmed that there is no liquid water around the CL and MPL. These suggest that the increase in oxygen transport resistance is caused by deterioration of oxygen permeability through the ionomer due to decrease in the water content. In addition, we tried to reduce oxygen transport resistance at higher current densities by controlling the balance between the vapor diffusion and heat conduction.